2019
DOI: 10.1136/oemed-2018-105672
|View full text |Cite
|
Sign up to set email alerts
|

Occupational exposure to organic particles and combustion products during pregnancy and birth outcome in a nationwide cohort study in Sweden

Abstract: ObjectiveTo study if children of women exposed to organic particles and combustion products at work during pregnancy, have an increased risk of low birth weight, preterm birth or small for gestational age.MethodsA nationwide cohort of all occupationally active mothers and their children from single births during 1994 to the end of 2012 (1 182 138 observations) was formed. Information on birth outcome was obtained from the medical birth register. Information on absence from work, education, occupation, age, nat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Exposures are described by the prevalence of exposure and the level of exposure among the exposed, both estimated mainly on continuous scales. FINJEM has been used for assessing occupational risk factors in many studies ( 32 , 33 ) and there are several derivates from FINJEM ( 20 ).…”
Section: Examples Of Job-exposure Matricesmentioning
confidence: 99%
“…Exposures are described by the prevalence of exposure and the level of exposure among the exposed, both estimated mainly on continuous scales. FINJEM has been used for assessing occupational risk factors in many studies ( 32 , 33 ) and there are several derivates from FINJEM ( 20 ).…”
Section: Examples Of Job-exposure Matricesmentioning
confidence: 99%
“…Although some studies suggested that maternal exposure to PAHs was not significantly associated with term low birth weight (LBW, birth weight less than 2500g), some studies have found negative impacts of maternal exposures to PAHs on birth weight [21][22][23][24][25][26][27]. A nationwide cohort study in Sweden has suggested that maternal occupational exposure to PAHs significantly increased the risk of LBW (OR:1.49, 95%CI: 1.27, 1.75) [28]. Another study found similar results that placental PAHs levels were negatively associated with birth weight (r: -0.223, P = 0.037) [29].…”
Section: Introductionmentioning
confidence: 99%